Ecotoxicological Assessment and Biodegradation Potential of Epoxidised Methyl Oleate (EMO) as a Bio-Based Plasticiser in Aquatic Environment - Siti Afida Ishak,; Asma Liyana Shaari,; Noorazah Zolkarnain,; Razmah Ghazali,; Zulina Abd Maurad, (Tropical Life Sciences Research, 2025)
Bio-based plasticisers have been developed as sustainable alternatives to phthalate-based plasticisers. However, limited information on their potential ecotoxicological effects on aquatic organisms could hinder their widespread adoption in the market. This study addresses this gap by providing ecotoxicological data on epoxidised methyl oleate (EMO), a potential bio-based plasticiser. This study evaluated the acute toxicity of EMO on five aquatic species (Moina macrocopa, Daphnia magna, Chlamydomonas reinhardtii, Chlorella vulgaris and Macrobrachium lanchesteri) to develop a species sensitivity distribution (SSD) curve for determining the predicted no-effect concentration (PNEC) of EMO for ecological risk assessment. Additionally, the biodegradation potential of EMO in aquatic environments was assessed using the OECD 301F Manometric Respiratory Test. These results indicate that EMO exhibits a concentration-dependent toxic effect on all tested species. The SSD curve, developed using a normal distribution and a Maximum Likelihood Estimation fit model, yielded 0.359 mg/L for hazardous concentration for 5% of species (HC05). This HC05 value suggests that EMO poses a minimal ecological risk, as it exceeded the water solubility limit (0.012 mg/L). Furthermore, EMO demonstrated favourable biodegradation potential under aerobic conditions. At a concentration of 30 mg/L, EMO achieved 60% biodegradation within four days of incubation, whereas at 100 mg/L, the same level of biodegradation was achieved by Day 11. These findings underscore the importance of assessing the environmental impact of bio-based plasticisers and highlight the EMO’s potential as an eco-friendly alternative to less biodegradable, petroleum-based plasticisers.